A microscopic theory of photonucleation: Density functional approach to the properties of a fluid of two-level atoms, a part of which is excited - Derzhko, O.; Myhal, V. (Condensed Matter Physics, 2006)
We use the density functional method to examine the properties of the nonuniform (two-phase) fluid of twolevel atoms, a part of which is excited. From the analysis of the equation of state of a gas of two-level atoms, a part of which is excited, the following density functional of the grand thermodynamical potential emerges width (here ΩCS[ρ(r)] is the Carnahan-Starling term, σ is the atom radius, v = 4/3πσ³, c₁ is the concentration of excited atoms, c₀ + c₁ = 1, E₁ − E₀ is the excitation energy and a is the dimensionless parameter which characterizes the atom). We use this expres